Arctic Networks and Legal Interpretations of the UN Commission on the Limits of the Continental Shelf. (30th October 2015) - GRABEN, SARI; HARRISON, PETER
Abstract: The United Nations Commission on the Limits of the Continental Shelf is expected to play an essential role in delineating the rights of the Arctic states to seabed resources in the Arctic Ocean. In this article, the authors look to the effect of scientific discourse on Commission authority. The authors argue that in addition to the conferral of its authority by the United Nations Convention on the Law of the Sea, the Commission draws its authority in the Arctic from the way its regulatory frameworks, aimed at containing or closing off disputes about jurisdiction and sovereign rights, correlate with discursive practices used by transnational networks to reach scientific agreement.